2022
DOI: 10.1371/journal.pone.0270065
|View full text |Cite
|
Sign up to set email alerts
|

The association of sun exposure, ultraviolet radiation effects and other risk factors for pterygium (the SURE RISK for pterygium study) in geographically diverse adult (≥40 years) rural populations of India -3rd report of the ICMR-EYE SEE study group

Abstract: Purpose To determine the prevalence and risk factors for pterygium in geographically diverse regions of India. Methods A population-based, cross-sectional multicentric study was conducted in adults aged ≥40 years in plains, hilly and coastal regions of India. All participants underwent a detailed questionnaire-based assessment for sun exposure, usage of sun protective measures, exposure to indoor smoke, and smoking. Detailed ocular and systemic examinations were performed. Pterygium was diagnosed and graded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…All included articles and the identified SDoH in each study are summarized in Table 1. Dry eye/ocular surface [18 ▪▪ ,19 ▪ –38 ▪ ] (21 articles) was the most prevalent cornea condition, followed by pterygium [39 ▪▪ ,40 ▪ –42 ▪ ] (4 articles), keratoplasty [43 ▪▪ ,44–46] (four articles), keratoconus [47 ▪ ,48,49] (three articles), cornea donation [50,51 ▪▪ ,52 ▪▪ ] (three articles), cornea thickness [53 ▪ ,54 ▪ ] (two articles), trachoma [55 ▪▪ ,56] (two articles), corneal ulcers [57 ▪ ,58 ▪ ] (two articles), corneal arcus [59 ▪ ] (one article), and corneal opacity[60 ▪ ] (one article). Cornea donation for transplantation was also explored.…”
Section: Search Results and Studies Included In The Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…All included articles and the identified SDoH in each study are summarized in Table 1. Dry eye/ocular surface [18 ▪▪ ,19 ▪ –38 ▪ ] (21 articles) was the most prevalent cornea condition, followed by pterygium [39 ▪▪ ,40 ▪ –42 ▪ ] (4 articles), keratoplasty [43 ▪▪ ,44–46] (four articles), keratoconus [47 ▪ ,48,49] (three articles), cornea donation [50,51 ▪▪ ,52 ▪▪ ] (three articles), cornea thickness [53 ▪ ,54 ▪ ] (two articles), trachoma [55 ▪▪ ,56] (two articles), corneal ulcers [57 ▪ ,58 ▪ ] (two articles), corneal arcus [59 ▪ ] (one article), and corneal opacity[60 ▪ ] (one article). Cornea donation for transplantation was also explored.…”
Section: Search Results and Studies Included In The Reviewmentioning
confidence: 99%
“…The observed social risk factors for education access and quality was limited to education achieved (educational level and literacy) [18 ▪▪ ,39 ▪▪ ]. This domain was explored for all of the cornea conditions.…”
Section: Education Access and Qualitymentioning
confidence: 99%
“…Pterygium is a fibro-vascular growth of actinically damaged conjunctiva encroaching upon the cornea, across the limbus within the interpalpebral fissure, commonly on the nasal side [ 1 ]. A recent Indian study found positive associations of pterygium with the coastal location, illiteracy, and increasing lifetime sun exposure.…”
Section: Introductionmentioning
confidence: 99%
“…A recent Indian study found positive associations of pterygium with the coastal location, illiteracy, and increasing lifetime sun exposure. They found a negative association of pterygium with BMI ≥ 25 kg/m2 [ 1 ]. Pterygium presents as an oculofacial cosmetic blemish and, in large size, may lead to optical anomalies like astigmatism due to the distortion of corneal topography [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pterygia has been linked to a number of risk factors, including geographic latitude, living in rural areas, aging, race, gender, sun exposure, chronic irritation, and inflammation. 2 After pterygium surgery, corneal irregularity is a crucial factor in preserving good visual acuity and function, and it takes time to restore the corneal surface [3] . According to Nejima et al 3 , a larger sized pterygium requires 6 to 12 months to stabilise corneal irregularity.…”
Section: Introductionmentioning
confidence: 99%